Brain Tumor Immunotherapy: What have We Learned so Far? - Van Gool, Stefaan Willy (Frontiers in Oncology, 2015)
High grade glioma (HGG) is a rare brain cancer, incurable in spite of modern neurosurgery, radiotherapy and chemotherapy. Novel approaches are in research, and immunotherapy emerges as a promising strategy. Clinical experiences with active specific immunotherapy demonstrate feasibility, safety and most importantly, but incompletely understood, prolonged long-term survival in a fraction of the patients. In relapsed patients, we developed an immunotherapy schedule and we categorized patients into clinically defined risk profiles. We learned how to combine immunotherapy with standard multimodal treatment strategies for newly diagnosed glioblastoma multiforme (GBM) patients. The developmental program allows further improvements related to newest scientific insights. Finally we developed a mode of care within academic centers to organize cell-based therapies for experimental clinical trials in a large number of patients.